The public sphere and representations of the self: radio talk shows in post-apartheid South Africa - Hungbo, Jendele (My University, 2012)
A vibrant media environment is fast becoming a prerequisite for democratic culture. Recent studies in radio in Africa have also paid attention to how the deregulation of the media space in the continent can be a catalyst to the growth of democratic culture. Yet, in so doing, current research pays less attention to the crucial aspect of self-fashioning which reflects power relations as well the existing relationships among individuals and different groups in society. This thesis examines the representation of the self on two ‘popular’ radio talk shows in contemporary South Africa. Using ‘The After Eight Debate’ and ‘The Redi Direko Show’ the thesis looks into the dynamics of representational politics which characterise the post-apartheid public sphere in South Africa. It deals with the way ‘imagined communities’ emerge through different kinds of discursive practices on radio talk shows and how participants react to different kinds of situations when they feature on radio. The study reveals access inequalities, performance and performative practices which translate to the silencing of various aspects of the self on radio talk shows. It concludes that the democratic credentials of radio talk shows are dwarfed by these silences which have the potential of privileging power and the power elite in contemporary South Africa.
Ph.D. University of the Witwatersrand, Faculty of Humanities 2012